2018
DOI: 10.1186/s12879-018-3603-x
|View full text |Cite
|
Sign up to set email alerts
|

Heart and liver are infected in fatal cases of dengue: three PCR based case studies

Abstract: BackgroundDengue is a global problem mainly in the tropics. Meticulous clinical management of cases has reduced the death rate significantly, but large numbers of people still succumb to severe complications of the infection. Presence of myocarditis is often overlooked leading to a poor outcome. Clinical management guidelines of dengue do not stress the importance of myocarditis as a manifestation in dengue infection. Severe hepatic dysfunction also needs emphasis.Case presentationWe present three patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Elevated levels of these enzymes are an early marker of DEN. Transaminase levels are higher in patients presenting DHF or DSS, and the increase is usually mild or moderate; however, an increase in enzyme levels of more than tenfold has been reported 20 , 22 , 84 . An increase in transaminase levels has also been seen in immunocompetent mice infected with DENV-2 19 , 57 , 59 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Elevated levels of these enzymes are an early marker of DEN. Transaminase levels are higher in patients presenting DHF or DSS, and the increase is usually mild or moderate; however, an increase in enzyme levels of more than tenfold has been reported 20 , 22 , 84 . An increase in transaminase levels has also been seen in immunocompetent mice infected with DENV-2 19 , 57 , 59 .…”
Section: Discussionmentioning
confidence: 93%
“…Liver involvement is commonly seen in DEN, and although more frequently associated with SD, it is also present in nonsevere cases of DEN 18 , 80 . Liver function abnormalities induced by DENV infection range from a mild rise in transaminase and bilirubin levels to acute liver failure, which may lead to death 22 , 81 , 82 . ALT and AST are considered indicators of liver abnormalities, as they are released into the bloodstream following liver cell injury 83 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When under observation with infection various clinical manifestations prevailed like acute GI bleeding, myocarditis, severe diarrhea, sepsis and occult bleeding. Another case study reported by Kularatne, Rajapakse, et al (2018) and Kularatne, Ralapanawa, et al (2018), revealed cases of involvement of vital organs like myocardium and hepatic system leading to complications, which was further proved as infection was DENV in the organs was evidenced by PCR technique. It has also revealed that dengue infection leads to meningoencephalitis, one of the neurological manifestations resulting in death of the patients (Soni, Das, George, Aggarwal, & Sivasankar, 2017).…”
Section: Need Of Therapeuticsmentioning
confidence: 84%
“…It first infects dendritic cells and then monocytes/macrophages, where it replicates and spreads infective particles that can reach different organs. Studies with patients that succumb to infection revealed that the virus can replicate in several organs, such as the liver, heart, lung, and brain (6)(7)(8). It interacts with different cell receptors through the E protein [reviewed in (9)].…”
Section: The Dengue Virus and Infectionmentioning
confidence: 99%